Dynamic changes of DNA methylation and lung disease in cystic fibrosis: lessons from a monogenic disease. (August 2018) - Magalhães, Milena; Tost, Jörg; Pineau, Fanny; Rivals, Isabelle; Busato, Florence; Alary, Nathan; Mely, Laurent; Leroy, Sylvie; Murris, Marlène; Caimmi, Davide; Claustres, Mireille; Chiron, Raphaël; et al.
Aim: To assess whether DNA methylation levels account for the noninherited phenotypic variations observed among cystic fibrosis (CF) patients.Patients & methods: Using the 450 K BeadChip, we profiled DNA methylation in nasal epithelial cells collected from 32 CF patients and 16 controls.Results: We detected substantial DNA methylation differences up to 55% (median β change 0.13; IQR: 0.15–0.11) between CF patients and controls. DNA methylation levels differed between mild and severe CF patients and correlated with lung function at 50 CpG sites.Conclusion: In CF samples, dynamic changes of DNA methylation occurred in genes responsible for the integrity of the epithelium and the inflammatory and immune responses, were prominent in transcriptionally active genomic regions and were over-represented in enhancers active in lung tissues. (Clinicaltrials.gov NCT02884622).